Health Problems among Women Building Construction Workers - Sultana, Nahid; Ferdousi, Jannatul; Shahidullah, Md (Journal of Bangladesh Society of Physiologist, 2015)
Back ground: Construction industry is one of the stable growing industries world over, including Bangladesh. In Dhaka city there are many construction sites, where workers are exposed to hazardous condition, specially the female workers. Throughout the world, over 90% of construction workers are male. In some developing countries, the proportion of women is higher. In Bangladesh their number is increasing day by day. Objective: To explore the health problems among the women building construction workers Methods: This cross-sectional study was carried out among 134 female construction workers. Data was collected through face to face interview by using prefixed questionnaire. The study was conducted from September 2011 to December 2012 in the Department of Community medicine, Dhaka National Medical College, Dhaka. The subjects were selected from different building construction sites of old Dhaka city. Results: It was observed that among 134 respondents, majority 96(71.6%) of the women construction worker were brick breaker and 38(28.3%) were weight carrier. Their mean age was 38.29±6.9 years. Most workers 110 (82.1%) had different types of skin problem. The proportion of skin problems was found to be high among the weight carrier and the difference was statistically highly significant (pOE .001). 89(66.5%) respondents had urinary tract infection, 66(49.3%) had constipation and 24(17.9%) complaint uterine prolapse. Among the total respondents 68(58.2%) complain of backache. The workers who complain of backache, 52(54.1%) were brick breaker and 16(42.1%) were weight carrier. 79 (58.9%) respondents used personal protective equipments, among them 61(77.2%) used self made hand gloves and 38(48.1%) used folded towel to carry weight. Besides of the total respondents 117(87.3%) complain of different types of respiratory problem. Conclusion: The study concludes that different types of skin diseases are present among female construction workers that might be attributable to exposure to hot humid working environment. Besides pain full micturation, uterine prolapse, low backache and respiratory problem were found among them which might need special attention. DOI: http://dx.doi.org/10.3329/jbsp.v9i1.22793 Bangladesh Soc Physiol. 2014, June; 9(1): 31-36